Prevention of Corruption in the Procurement Process of Government Goods and Services in The Digital Era - Parningotan Malau (Universitas Sultan Ageng Tirtayasa, 2022)
The purpose of this research is to undertake a legal analysis of the anti-corruption procurement process for government goods and services through the use of good governance. The research approach employed in this study is a normative juridical one, which involves studying legislative rules and examining corrupt activities that occur in the sphere of procurement of goods and services. The sources of law in this study are material law sources and traditional legal sources. Based on the analysis of legal authorities, it can be concluded that the criminal act of corruption in the procurement of government goods and services has violated the regulations in Article 2 paragraph (1) of Law No. 31 of 1999 and Law No. 20 of 2001 on Corruption. The implementation of good governance in preventing corruption in the procurement of goods and services is seen from two aspects, namely internal and external aspects. Internal elements include improving the quality of internal resources in government organizations and increasing accountability and transparency. In contrast, external elements increase community participation, legitimacy, and anti-corruption socialization through various media.